Silicon-carbon composite materials and their preparation methods, negative electrode sheets, secondary batteries and electrical devices
Patent Information
- Application Number
- CN202380060813.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-04-04
AI Technical Summary
Silicon-based negative active materials have large volume expansion in secondary batteries, which affects electrochemical performance, and existing silicon-carbon composite materials have poor conductivity, limiting their application.
The silicon-carbon composite material formed by combining a porous carbon skeleton with silicon-based materials and doping elements (such as Sn, Ge, Sb, Bi), uniformly disperses silicon particles in the porous carbon skeleton and controls the mass fraction and doping elements. grain size, improve conductivity and structural stability, and reduce lithium ion migration barrier.
Significantly reduce the fast charging time of the battery, improve the rate performance and cycle number, extend the cycle life of the battery, and comprehensively improve the electrochemical performance of the battery.
Smart Images

Figure CN119768935A_ABST
Abstract
Description
Silicon-carbon composite material, preparation method thereof, negative electrode sheet, secondary battery and electrical device Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a silicon-carbon composite material, a preparation method thereof, a negative electrode sheet, a secondary battery, and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] Negative electrode active materials are important components of secondary batteries. In order to further improve the energy density of batteries, silicon-based negative electrode active materials have been widely studied. However, due to their large volume expansion, silicon-based materials will affect the electrochemical performance of the battery during use.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a silicon-carbon composite material, which has excellent electron transmission performance, is beneficial to reducing the fast charging time of the battery, increasing the number of cycles of the battery, and can improve the rate performance and cycle performance of the battery, thereby comprehensively improving the electrochemical performance of the battery.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a silicon-carbon composite material, including a porous carbon skeleton; a silicon-based material, at least partially arranged in the pores of the porous carbon skeleton; and a doping element, at least part of which is distributed in the porous carbon skeleton; wherein the doping element satisfies: the lithium ion diffusion coefficient of the doping element at 25°C is greater than the lithium ion diffusion coefficient of silicon at 25°C.
[0007] On the one hand, the silicon-carbon composite material has a stable porous skeleton structure with strong supporting capacity, which is manifested as high stress capacity, and has excellent mechanical properties and conductivity; the pore structure in its porous carbon skeleton provides more space for setting silicon particles, which can be used for large-scale silicon storage; when the porous carbon skeleton is compounded with silicon particles, the silicon particles are not easy to agglomerate and can be evenly dispersed in the pores of the porous carbon skeleton; after the porous carbon skeleton is compounded with silicon particles, the conductivity of the silicon-carbon composite material can be improved, and at the same time, the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and it can fully withstand the stress changes of silicon-based materials, ensure the structural stability of the silicon-carbon composite material, improve the cycle stability and lithium storage capacity of the silicon-carbon composite material, and extend the cycle life of the battery; on the other hand, doping the silicon-carbon composite material with an element whose lithium ion diffusion coefficient is greater than that of silicon element is beneficial to reducing the migration barrier and migration energy of lithium ions in the silicon-carbon composite material, greatly improving the lithium ion solid-phase diffusion coefficient of the silicon-carbon composite material, improving the migration kinetics of lithium ions, shortening the fast charging time of the battery, and improving the rate performance of the material.
[0008] In any embodiment, the lithium ion diffusion coefficient of the single substance of the doping element at 25°C is greater than 10 -14 cm 2 / S, can be greater than 10 -14 cm 2 / S and less than or equal to 10 - 13 cm 2 / S; and / or, the lithium ion diffusion coefficient of the silicon element at 25°C is less than 10 - 14 cm 2 / S, can be greater than 10 -15 cm 2 / S and less than 10 -14 cm 2 / S.
[0009] In any embodiment, the doping element includes at least one of Sn, Ge, Sb, Bi, and Sr.
[0010] The lithium ion diffusion coefficients of the above-mentioned doping elements at 25°C are all greater than the lithium ion diffusion coefficient of silicon at 25°C, and can all be doped into the silicon-carbon composite material, thereby reducing the migration barrier and migration energy of lithium ions in the silicon-carbon composite material, increasing the lithium ion solid-phase diffusion coefficient of the silicon-carbon composite material, improving the migration kinetics of lithium ions, improving the rate performance of the battery, and improving the kinetic performance of the battery.
[0011] In any embodiment, at least part of the doping elements forms grains in the silicon-carbon composite material; optionally, the size of the grains is less than or equal to 10 nm, and more optionally 3 nm to 7 nm.
[0012] The doping elements exist in the silicon-carbon composite material in the form of crystals. Compared with the doping elements in amorphous form, the crystal state can effectively improve the electrical and ionic conductivity of the doping elements, further improve the conductivity of the material, and improve the rate performance of the battery. In addition, controlling the grain size of the doping elements formed in the silicon-carbon composite material within an appropriate range is conducive to reducing the migration barrier and migration energy of lithium ions in the silicon-carbon composite material, significantly improving the lithium ion solid phase diffusion coefficient of the silicon-carbon composite material, improving the lithium ion migration kinetics, and improving the rate performance of the battery. In addition, the doping elements exist in the form of small-sized crystals, which will not cause major changes in the silicon-carbon structure or the phase characteristics of the material. It can well maintain the structural stability of the material, is not easy to pulverize during the charge and discharge process, improves the cycle performance of the battery, and extends the cycle life of the battery.
[0013] In any embodiment, based on the total mass of the silicon-carbon composite material, the mass fraction of the doping element is less than or equal to 7%, and can be optionally 1%-3%.
[0014] Controlling the mass fraction of doping elements within an appropriate range can not only reduce the migration barrier and migration energy of lithium ions in silicon-carbon composites, significantly improving the solid-phase diffusion coefficient of lithium ions in silicon-carbon composites, but also avoid excessively high doping element mass fractions that can alter the material's internal structure and affect battery cycle performance. Doping elements within an appropriate mass content range can balance battery rate performance and cycle performance, comprehensively improving battery performance.
[0015] In any embodiment, the porous carbon framework is spherical or spherical-like.
[0016] The spherical or quasi-spherical porous carbon skeleton is conducive to forming a smooth void structure in the negative electrode film layer, improving the solid-phase diffusion rate and liquid-phase transmission performance of lithium ions, enhancing the battery's fast charging capability, and improving the battery's rate performance.
[0017] In any embodiment, based on the total mass of the silicon-carbon composite material, the mass fraction of the silicon-based material is greater than or equal to 30%, and can be optionally 35%-50%; and / or, based on the total mass of the silicon-carbon composite material, the mass fraction of the porous carbon skeleton is greater than or equal to 30%, and can be optionally 40%-60%.
[0018] The mass content of the silicon-based material is within an appropriate range, so that the silicon-carbon composite material has a high gram capacity, which improves the energy density of the battery. At the same time, the volume expansion of the silicon-carbon composite material is limited to a certain range, so that the silicon-carbon composite material has a certain structural stability.
[0019] Controlling the mass fraction of silicon-based materials within an appropriate range can take into account both the cycle performance and energy density of the battery.
[0020] The mass content of the porous carbon skeleton is within a suitable range, so that the silicon-carbon composite material has a sufficient porous carbon skeleton to accommodate the silicon-based material and the doping elements, and the silicon-based composite material has a high gram capacity. At the same time, the mass content of the porous carbon skeleton is within a suitable range, which can improve the conductivity of the silicon-carbon composite material and improve the kinetic performance of the battery.
[0021] Controlling the mass fraction of silicon-based materials within an appropriate range can take into account the battery's cycle performance, rate performance and energy density.
[0022] In any embodiment, the volume distribution particle size Dv50 of the silicon-carbon composite material is less than or equal to 5 μm, and can be optionally 1 μm-3 μm.
[0023] Controlling the volume distribution particle size Dv50 of the silicon-carbon composite material within an appropriate range is beneficial to further reducing the solid-phase migration path of lithium ions in the silicon-carbon composite material and improving the battery rate performance.
[0024] In any embodiment, the silicon-carbon composite material satisfies at least one of the following (1)-(4):
[0025] (1) The specific surface area of the porous carbon skeleton is 1000 m 2 / g-2500m 2 / g;
[0026] (2) The pore size of the porous carbon skeleton is 0.5nm-100nm;
[0027] (3) The pore volume of the porous carbon skeleton is 0.5 cm 3 / g-8.5cm 3 / g;
[0028] (4) The volume distribution particle size Dv50 of the porous carbon skeleton is 0.3μm-5μm.
[0029] Controlling the specific surface area, pore size, pore volume and particle size of the porous carbon skeleton within an appropriate range facilitates the uniform distribution of silicon-based materials and doping elements, and the battery has excellent cycle performance and rate performance, and the battery has a high energy density.
[0030] In any embodiment, the silicon-carbon composite material has a carbon layer on at least a portion of its surface.
[0031] The carbon layer coated on the silicon-carbon composite material is beneficial to improving the conductivity of the silicon-carbon composite material and improving the rate performance of the material. At the same time, the carbon layer can also enhance the stability between the silicon-carbon composite material and the electrolyte and improve the cycle performance of the battery.
[0032] A second aspect of the present application provides a method for preparing a silicon-carbon composite material, comprising the following steps:
[0033] Preparing a porous carbon skeleton containing a doping element, wherein the doping element satisfies: a lithium ion diffusion coefficient of the doping element at 25° C. is greater than a lithium ion diffusion coefficient of silicon at 25° C.;
[0034] A silicon-based material is deposited in the pores of the porous carbon skeleton to obtain the silicon-carbon composite material.
[0035] On the one hand, the silicon-carbon composite material obtained in the above preparation method has a stable porous skeleton structure, and its supporting capacity is strong, which is manifested as high stress capacity, and has excellent mechanical properties and electrical conductivity; the pore structure in its porous carbon skeleton provides more space for setting silicon particles, which can be used for large-scale silicon storage; when the porous carbon skeleton is compounded with silicon particles, the silicon particles are not easy to agglomerate and can be evenly dispersed in the pores of the porous carbon skeleton. After the porous carbon skeleton is compounded with silicon particles, the electrical conductivity of the silicon-carbon composite material can be improved, and at the same time, the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and it can fully withstand the stress changes of silicon-based materials, ensure the structural stability of the silicon-carbon composite material, improve the cycle stability and lithium storage capacity of the silicon-carbon composite material, and extend the cycle life of the battery; on the other hand, doping the silicon-carbon composite material with an element whose lithium ion diffusion coefficient is greater than that of silicon element is beneficial to reducing the migration barrier and migration energy of lithium ions in the silicon-carbon composite material, greatly improving the lithium ion solid-phase diffusion coefficient of the silicon-carbon composite material, improving the migration kinetics of lithium ions, and improving the battery rate performance.
[0036] In any embodiment, the preparation of the porous carbon skeleton includes solvent thermal reaction, activation pore formation and high temperature carbonization.
[0037] Solvothermal reaction: mixing a resin containing an unsaturated group and / or a sugar, a solvent, and an aqueous solution containing a doping element, and performing a solvothermal reaction to obtain a first product;
[0038] Activation pore creation: introducing water vapor into the first product to perform activation pore creation treatment to obtain the second product;
[0039] High-temperature carbonization: The second product is subjected to high-temperature carbonization treatment to obtain a porous carbon skeleton.
[0040] The above preparation method can obtain a porous carbon skeleton, and the preparation method is simple and easy to industrially apply.
[0041] In any embodiment, the reaction temperature of the solvothermal reaction is 400° C.-750° C.; and / or the reaction time of the solvothermal reaction is 4 h-10 h.
[0042] By controlling the reaction time and / or reaction temperature within a suitable range, the structural parameters of the porous carbon skeleton, such as the volume distribution particle size Dv50, specific surface area, pore size and pore volume, can be controlled within a suitable range, which is beneficial to the subsequent deposition of silicon-based materials.
[0043] In any embodiment, the mass ratio of the resin containing unsaturated groups to the saccharide is (2:8)-(9:1), and can be optionally (4:6)-(6:4).
[0044] The molar ratio of the resin containing unsaturated groups to the saccharide is controlled within a suitable range so that the porous carbon skeleton has a suitable specific surface area, pore size, pore volume and particle size, which is beneficial to the subsequent deposition of silicon.
[0045] In any embodiment, the resin containing unsaturated groups includes at least one of phenolic resin, furfural resin, and lignin-based activated carbon; and / or the sugar includes at least one of sucrose, glucose, and chitosan.
[0046] In any embodiment, the treatment temperature for activation pore creation is 400° C.-500° C.; and / or, the treatment time for activation pore creation is 4 h-8 h; and / or, the flow rate of the water vapor is 0.5 g / min-1 g / min.
[0047] In any embodiment, the deposition temperature of the vapor-deposited silicon is 500° C.-900° C.; and / or the deposition time of the vapor-deposited silicon is 6 h-24 h.
[0048] By controlling the deposition time and temperature of vapor-deposited silicon within a suitable range, silicon is uniformly dispersed in the pores of the porous carbon skeleton, and the silicon-carbon composite material has excellent structural parameters.
[0049] In any embodiment, the preparation method further comprises preparing a carbon layer,
[0050] Preparation of carbon layer: performing carbon coating treatment on the surface of silicon-carbon composite material.
[0051] Coating the surface of the silicon-carbon composite material with a carbon layer is beneficial to improving the conductivity of the silicon-carbon composite material and improving the rate performance of the material. At the same time, the carbon layer can also enhance the stability between the silicon-carbon composite material and the electrolyte, thereby improving the cycle performance of the battery.
[0052] The third aspect of the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer arranged on the surface of the negative electrode current collector, the negative electrode film layer includes a negative electrode active material, and the negative electrode active material includes the silicon-carbon composite material described in the first aspect of the present application or the silicon-carbon composite material prepared according to the preparation method described in the second aspect of the present application.
[0053] A fourth aspect of the present application provides a secondary battery, comprising the negative electrode sheet according to the third aspect of the present application.
[0054] A fifth aspect of the present application provides an electrical device comprising the secondary battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application.
[0056] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 1 .
[0057] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0058] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.
[0059] FIG. 5 is an exploded view of the battery pack shown in FIG. 4 according to an embodiment of the present application.
[0060] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0061] FIG7 is a scanning electron microscope image of the porous carbon skeleton shown in Example 1 of the present application.
[0062] Explanation of reference numerals: 1 battery pack; 2 upper housing; 3 lower housing; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION
[0063] Hereinafter, the silicon-carbon composite material of the present application, its preparation method, negative electrode sheet, secondary battery and electric device are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0064] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed in this application, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0065] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0066] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0067] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0068] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0069] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0070] Silicon-carbon composites are one of the most commonly used active materials. Currently, their preparation primarily involves directly mixing silicon with carbon materials. These materials have certain limits on the silicon content. Excessive silicon content can lead to significant expansion, which can damage the electrode structure and deteriorate the battery's cycle life. Furthermore, the poor electrical conductivity of the composite itself severely limits its further application. Therefore, a new silicon-carbon composite material is needed to meet the needs of the next generation of electrochemistry.
[0071] [Silicon-carbon composite materials]
[0072] Based on this, the present application proposes a silicon-carbon composite material, including a porous carbon skeleton; a silicon-based material, at least part of the silicon-based material is arranged in the pores of the porous carbon skeleton; and a doping element, at least part of the doping element is distributed in the porous carbon skeleton; wherein the doping element satisfies: the lithium ion diffusion coefficient of the doping element at 25°C is greater than the lithium ion diffusion coefficient of the silicon element at 25°C.
[0073] On the one hand, the silicon-carbon composite material has a stable porous skeleton structure with strong supporting capacity, which is manifested as high stress capacity, and has excellent mechanical properties and conductivity; the pore structure in its porous carbon skeleton provides more space for the deposition of silicon particles, which can be used for large-scale silicon storage; when silicon is deposited on the porous carbon skeleton, the silicon particles are not easy to agglomerate and can be evenly dispersed in the pores of the porous carbon skeleton; after the porous carbon skeleton is compounded with silicon particles, the conductivity of the silicon-carbon composite material can be improved, and the rate performance of the material can be improved. At the same time, the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and it can fully withstand the stress changes of silicon particles to ensure the structural stability of the silicon-carbon composite material; on the other hand, doping the silicon-carbon composite material with an element whose lithium ion diffusion coefficient is greater than that of silicon element is beneficial to reducing the migration barrier and migration energy of lithium ions in the silicon-carbon composite material, greatly improving the lithium ion solid-phase diffusion coefficient of the silicon-carbon composite material, improving the migration kinetics of lithium ions, and improving the rate performance of the material.
[0074] In summary, the silicon-carbon composite material of the present application can reduce the fast charging time of the battery, improve the rate performance of the battery, increase the number of cycles of the battery, extend the cycle life of the battery, and comprehensively improve the performance of the battery.
[0075] In the present application, the term "silicon-carbon composite material" refers to a material in which the mass content of silicon and carbon elements is greater than 10% based on the total mass of the silicon-carbon composite material.
[0076] In the present application, the term "porous carbon skeleton" means that the main component of the skeleton is carbon and the skeleton contains multiple pores.
[0077] The porous carbon skeleton structure of the silicon-carbon composite material can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the negative electrode sheet containing the silicon-carbon composite material is cut into a sample to be tested of a certain size (for example, 6mm×6mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheet are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400g) is used to press for a certain time (such as 1h) so that the gap between the sample to be tested and the copper foil is as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, and the sample slightly protrudes from the edge of the sample table. Then, place the sample stage into the sample holder and lock it securely. Turn on the power of the argon ion cross-section polisher (e.g., IB-19500CP) and evacuate the sample. Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours). Adjust the sample stage to rocking mode and start polishing. After polishing, use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain an ion polished cross-section morphology (CP) image of the sample to be tested.
[0078] In this application, "lithium ion diffusion coefficient" refers to an important parameter used to characterize the kinetic behavior of a material. The larger the diffusion coefficient of a material, the better the high-current discharge capability of the battery, the higher the power density of the material, and the better the high-rate performance.
[0079] The type of "doping element" in the present application refers to an element whose lithium ion diffusion coefficient of a simple substance formed by the element is greater than the lithium ion diffusion coefficient of a simple substance of silicon.
[0080] The lithium ion diffusion coefficient of a material has a well-known meaning in the art and can be measured using methods known in the art. As an example, this application uses a constant current intermittent titration (GITT) method to measure the lithium ion diffusion coefficient of a single material composed of a doping element.
[0081] In some embodiments, the lithium ion diffusion coefficient of the doping element at 25°C is greater than 10 -14 cm 2 / S, can be greater than 10 -14 cm 2 / S and less than or equal to 10-13 cm 2 / S.
[0082] In some embodiments, the lithium ion diffusion coefficient of silicon at 25°C is less than 10 - 14 cm 2 / S, can be greater than 10 -15 cm 2 / S and less than 10 -14 cm 2 / S.
[0083] In some embodiments, the lithium ion diffusion coefficient of the doping element at 25°C can be 2×10 -14 cm 2 / S, 3×10 -14 cm 2 / S, 4×10 -14 cm 2 / S, 5×10 - 14 cm 2 / S, 6×10 -14 cm 2 / S、7×10 -14 cm 2 / S, 8×10 -14 cm 2 / S, 9×10 - 14 cm 2 / S, 10 -13 cm 2 Any value in / S or a range of any two values in it.
[0084] In some embodiments, the lithium ion diffusion coefficient of silicon at 25°C may be 2×10 -15 cm 2 / S, 3×10 -15 cm 2 / S, 4×10 -15 cm 2 / S, 5×10 -15 cm 2 / S, 6×10 - 15 cm 2 / S、7×10 -15 cm 2 / S, 8×10 -15 cm 2 / S, 9×10 -15 cm 2 Any value in / S or a range of any two values in it.
[0085] In some embodiments, the doping element includes at least one of Sn, Ge, Sb, Bi, and Sr.
[0086] In some embodiments, the doping element includes at least two of Sn, Ge, Sb, Bi, and Sr. For example, the doping element may include Sn and Ge, Sn and Sb, Sn and Bi, Sn and Sr, Ge and Sb, Ge and Bi, Ge and Sr, Sb and Bi, Sb and Sr, or Bi and Sr.
[0087] These doping elements have excellent lithium-ion diffusion coefficients, effectively improving the conductivity of silicon-carbon composites and boosting the rate performance of batteries. Furthermore, the raw materials are abundant and readily available, making them suitable for use in a variety of batteries and offering excellent application prospects.
[0088] In some embodiments, at least a portion of the doping element forms grains in the silicon-carbon composite material.
[0089] Compared with doping elements in amorphous form, doping elements in crystalline form have better electronic and ionic conductivity, which can effectively improve the conductivity of silicon-carbon composite materials and improve the rate performance of batteries.
[0090] In some embodiments, the size of the grains is less than or equal to 10 nm.
[0091] The size of the grains is well known in the art and can be tested by methods known in the art. As an example, an X-ray powder diffractometer (XRD) is used to test the grain size formed by the doping elements in the carbon and silicon elements in the silicon-carbon composite material. The model of the X-ray powder diffractometer is the American X'pertPROo. The detailed test process of the grain size is as follows: a. Measurement of the actual width Bm of the silicon-carbon composite material sample. Set the instrument scanning rate to 2 degrees / minute, obtain the XRD spectrum of the sample to be tested, use the JADE software to deduct the CuKa2 background, and obtain the Bm of each diffraction peak; b. Instrument broadening Bs measurement. Use the same material as the silicon-carbon composite material sample and the grain size is Under the same experimental conditions as the silicon-carbon composite material sample, measure the XRD pattern of the standard sample and obtain Bs from the pattern; c. Calculate the half-height width, B. B = Bm - Bs; (Note: If the calculated unit of B is angle, it must be converted to radians). d. Calculate the grain size: Use the Scherrer formula D = Kλ / Bcosθ, where K is 0.89, θ is the diffraction angle, and λ = 0.154056nm. Substituting B into the formula, the grain thickness in the normal direction of the crystal plane represented by a single diffraction peak can be obtained. The grain size can be obtained by averaging the calculated values for multiple diffraction peaks.
[0092] In some embodiments, the size of the grains may be selected to be any one of less than or equal to 0.1 nm, less than or equal to 0.5 nm, less than or equal to 1 nm, less than or equal to 1.5 nm, less than or equal to 2 nm, less than or equal to 2.5 nm, less than or equal to 3 nm, less than or equal to 3.5 nm, less than or equal to 4 nm, less than or equal to 4.5 nm, less than or equal to 5 nm, less than or equal to 5.5 nm, less than or equal to 6 nm, less than or equal to 6.5 nm, less than or equal to 7 nm, less than or equal to 7.5 nm, less than or equal to 8 nm, less than or equal to 8.5 nm, less than or equal to 9 nm, less than or equal to 9.5 nm, or less than or equal to 10 nm.
[0093] Controlling the grain size of the doping elements in the silicon-carbon composite material within an appropriate range is beneficial for reducing the migration barrier and migration energy of lithium ions in the silicon-carbon composite material, significantly increasing the solid-phase diffusion coefficient of lithium ions in the silicon-carbon composite material, improving the lithium ion migration kinetics, and improving the rate performance of the battery. In addition, the presence of doping elements in the form of small-sized grains will not cause major changes in the silicon-carbon structure or the phase properties of the material. It can well maintain the structural stability of the material, is not easy to pulverize during the charge and discharge process, improves the cycle performance of the battery, and extends the cycle life of the battery.
[0094] In some embodiments, the size of the grains may be selected to be 3 nm to 7 nm.
[0095] In some embodiments, the size of the grains may be 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, or a value in a range consisting of any two of the above points.
[0096] Controlling the grain size within an appropriate range is beneficial to further increase the battery's cycle number and discharge time, reduce the battery's fast charging time, and further improve the battery's rate performance and cycle performance.
[0097] In some embodiments, the mass fraction of the doping element is less than or equal to 7%, based on the total mass of the silicon-carbon composite material.
[0098] The mass content of the doping element can be tested using methods and equipment known in the art, for example, with reference to EPA 6010D-2014 standard. Specifically, ICP-OES (elemental analysis - inductively coupled plasma optical emission spectrometry) testing can be used. The sample to be tested is first dissolved in a strong acid to form a liquid. The liquid is then introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then return to the ground state from the excited state. In this process, energy is released and recorded as different characteristic spectral lines for elemental quantitative analysis.
[0099] In some embodiments, based on the total mass of the silicon-carbon composite material, the mass fraction of the doping element can be selected as any one of less than or equal to 1%, less than or equal to 1.5%, less than or equal to 2%, less than or equal to 2.5%, less than or equal to 3%, less than or equal to 3.5%, less than or equal to 4%, less than or equal to 4.5%, less than or equal to 5%, less than or equal to 5.5%, less than or equal to 6%, less than or equal to 6.5%, and less than or equal to 7%.
[0100] Doping elements with an appropriate mass content can improve the electrical conductivity of silicon-carbon composite materials, improve the lithium ion transmission capacity of the material, and improve the cycle performance and rate performance of the battery. At the same time, doping elements with an appropriate mass content will not change the internal structure and crystal phase of the material, thereby improving the cycle performance of the battery.
[0101] In some embodiments, the mass fraction of the doping element is 1%-3%, based on the total mass of the silicon-carbon composite material.
[0102] In some embodiments, based on the total mass of the silicon-carbon composite material, the mass fraction of the doping element may be 1%, 1.5%, 2%, 2.5%, 3%, or a value in a range consisting of any two of the above values.
[0103] Controlling the mass content of the doping elements within an appropriate range is beneficial to further increase the battery's cycle times and discharge time, reduce the battery's fast charging time, and further improve the battery's rate performance and cycle performance.
[0104] In some embodiments, the porous carbon framework is spherical or spherical-like.
[0105] In this application, the term "spherical" means that the distance from the center of the sphere to any point on the sphere is equal.
[0106] In this application, the term "quasi-spherical" means that the distance from the center of the sphere to the farthest point of the sphere is R1, the distance from the center of the sphere to the closest point of the sphere is R2, and the absolute value of the difference between R1 and R2 divided by the average value of R1 and R2 is less than 1%.
[0107] The spherical or quasi-spherical porous carbon skeleton is conducive to forming a smooth void structure in the negative electrode film layer, improving the solid-phase diffusion rate and liquid-phase transmission performance of lithium ions, enhancing the battery's fast charging capability, and improving the battery's rate performance.
[0108] In some embodiments, the mass fraction of the silicon-based material is greater than or equal to 30%, based on the total mass of the silicon-carbon composite material.
[0109] The mass content of silicon-based materials can be tested using methods and equipment known in the art, for example, it can be measured with reference to EPA 6010D-2014 standard; specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used. The sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then return to the ground state from the excited state; in the above process, energy is released and recorded as different characteristic spectral lines for elemental quantitative analysis.
[0110] In some embodiments, based on the total mass of the silicon-carbon composite material, the mass fraction of the silicon-based material may be any one of greater than or equal to 30%, greater than or equal to 40%, greater than or equal to 45%, and greater than or equal to 50%.
[0111] The mass content of the silicon-based material is within an appropriate range, which makes the silicon-carbon composite material have a high gram capacity, improves the energy density of the battery, and at the same time limits the volume expansion of the silicon-carbon composite material to a certain range, so that the silicon-carbon composite material has a certain structural stability, and the battery has a high energy density and excellent cycle performance.
[0112] In some embodiments, the mass fraction of the silicon-based material is 35%-50%, based on the total mass of the silicon-carbon composite material.
[0113] In some embodiments, based on the total mass of the silicon-based composite material, the mass fraction of the silicon-based material can be selected as 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, or a value in the range consisting of any two of the above points.
[0114] Controlling the mass fraction of silicon-based materials within an appropriate range can balance the energy density and cycle life of the battery and comprehensively improve the performance of the battery.
[0115] In some embodiments, the mass fraction of the porous carbon framework is greater than or equal to 30%, based on the total mass of the silicon-carbon composite material.
[0116] In some embodiments, based on the total mass of the silicon-carbon composite material, the mass fraction of the porous carbon skeleton can be selected as any one of greater than or equal to 30%, greater than or equal to 40%, greater than or equal to 45%, and greater than or equal to 50%.
[0117] The mass content of the porous carbon skeleton can be tested using methods and equipment known in the art, for example, it can be measured with reference to the EPA 6010D-2014 standard; specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used, wherein the sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then restored to the ground state from the excited state; in the above process, energy is released and recorded as different characteristic spectral lines for elemental quantitative analysis.
[0118] The mass content of the porous carbon skeleton is within a suitable range, so that the silicon-carbon composite material has a sufficient porous carbon skeleton to accommodate the silicon-based material and the doping elements, and the silicon-based composite material has a high gram capacity. At the same time, the mass content of the porous carbon skeleton is within a suitable range, which can improve the conductivity of the silicon-carbon composite material and improve the kinetic performance of the battery.
[0119] In some embodiments, based on the total mass of the silicon-carbon composite material, the mass fraction of the porous carbon framework may be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, or a value in a range consisting of any two of the foregoing values.
[0120] Controlling the mass fraction of the porous carbon skeleton within an appropriate range can take into account the battery's cycle performance, rate performance and energy density.
[0121] In some embodiments, the volume distribution particle size Dv50 of the silicon-carbon composite material is less than or equal to 5 μm.
[0122] In some embodiments, the volume distribution particle size Dv50 of the silicon-carbon composite material can be selected as any one of less than or equal to 1 μm, less than or equal to 1.5 μm, less than or equal to 2 μm, less than or equal to 2.5 μm, less than or equal to 3 μm, less than or equal to 3.5 μm, less than or equal to 4 μm, less than or equal to 4.5 μm, and less than or equal to 5 μm.
[0123] The volume distribution particle size Dv50 of the silicon-carbon composite material is well known in the art and can be measured using methods known in the art. As an example, for example, a silicon-carbon composite material sample is measured according to the GB / T 19077-2016 / ISO 13320:2009 standard, and the testing equipment can be a laser particle size analyzer (such as the Malvern Master Size 3000).
[0124] The volume distribution particle size Dv50 of the silicon-carbon composite material is controlled to be less than or equal to 5 μm, so that the silicon-carbon composite material has a shorter lithium ion solid phase migration path, further improving the rate performance of the battery and improving the kinetic performance of the battery.
[0125] In some embodiments, the volume distribution particle size Dv50 of the silicon-carbon composite material is 1 μm-3 μm.
[0126] In some embodiments, the volume distribution particle size Dv50 of the silicon-carbon composite material can be selected as 1 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.8 μm, 3 μm, or a value in the range consisting of any two of the above points.
[0127] Controlling the volume distribution particle size Dv50 of the silicon-carbon composite material to 1μm-3μm is beneficial to further improve the discharge time of the battery and reduce its fast charging time, improve the battery's rate performance, and improve the battery's dynamic performance.
[0128] In some embodiments, the porous carbon skeleton has a specific surface area of 1000 m 2 / g-2500m 2 / g.
[0129] In some embodiments, the specific surface area of the porous carbon skeleton can be 1000 m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g、2000m 2 / g、2100m 2 / g、2200m 2 / g、2300m 2 / g、2400m 2 / g、2500m 2 / g or a value within the range consisting of any two of the above points.
[0130] The specific surface area of a porous carbon framework is well known in the art and can be measured using methods known in the art. As an example, the specific surface area of a porous carbon framework was measured using a 3Flex surface area analyzer from Micromeritics. The specific surface area of the porous carbon framework was obtained by T-Plot fitting (BET).
[0131] Controlling the specific surface area of the porous carbon skeleton within an appropriate range can shorten the migration distance of lithium ions and improve the rate performance of the battery. In addition, a suitable specific surface area can also expose more lithium ion reaction active sites, increase the gram capacity of the electrode, and increase the energy density of the battery. At the same time, a specific surface area within an appropriate range can also reduce the side reactions between the electrolyte and the material, and reduce the loss of irreversible capacity.
[0132] In some embodiments, the porous carbon framework has a pore size of 0.5 nm to 100 nm.
[0133] In some embodiments, the pore size of the porous carbon skeleton can be selected as 0.5nm, 1nm, 2nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm or a value in the range consisting of any two of the above points.
[0134] The pore size of a porous carbon framework is well known in the art and can be measured using instruments and methods known in the art. As an example, a certain amount of the porous carbon framework prepared above is taken as a sample and analyzed using a scanning electron microscope (SEM) to obtain an SEM image. The pore sizes are then statistically analyzed to create a normal distribution curve. The median pore size on the normal distribution curve is the pore size of the porous carbon framework.
[0135] The pore size of the porous carbon skeleton is within an appropriate range, which is conducive to the subsequent silicon particles entering the pores of the porous carbon skeleton, reducing the risk of silicon deposition on the surface of the porous carbon skeleton; and is conducive to the porous carbon skeleton particles approaching full deposition, improving the material's electrical and ionic conductivity, and improving the material's rate performance.
[0136] In some embodiments, the pore volume of the porous carbon framework is 0.5 cm 3 / g-8.5cm 3 / g.
[0137] In some embodiments, the pore volume of the porous carbon framework can be selected to be 0.5 cm 3 / g, 1cm 3 / g, 1.5cm 3 / g, 2cm 3 / g, 2.5cm 3 / g, 3cm 3 / g, 3.5cm 3 / g, 4cm 3 / g, 4.5cm 3 / g, 5cm 3 / g, 5.5cm 3 / g, 6cm 3 / g, 6.5cm 3 / g、7cm 3 / g, 7.5cm 3 / g、8cm 3 / g, 8.5cm 3 / g or a value within the range consisting of any two of the above points.
[0138] The pore volume of a porous carbon framework is well known in the art and can be measured using instruments and methods known in the art. For example, the pore volume of the material can be determined by referring to GB / T 19587-2004, using the Barret Joyner Halenda (BJH) mesopore size distribution method, using a gas adsorption-desorption method under a micro-mesoporous model and selecting adsorption branch data.
[0139] The pore volume of the porous carbon skeleton is within an appropriate range, which can not only ensure the stability of the skeleton structure but also meet the capacity of deposited silicon. Silicon particles are attached to the pores, and the silicon particles and the porous carbon skeleton can work synergistically to improve the capacity and conductivity of the silicon-carbon composite material, and improve the rate performance and energy density of the battery.
[0140] In some embodiments, the volume distribution particle size Dv50 of the porous carbon framework is 0.3 μm to 5 μm.
[0141] In some embodiments, the volume distribution particle size Dv50 of the porous carbon skeleton can be selected as 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm or a value in the range consisting of any two of the above points.
[0142] The volume distribution particle size Dv50 of the porous carbon skeleton is well known in the art and can be measured using methods known in the art. For example, the porous carbon skeleton sample is measured according to the GB / T 19077-2016 / ISO 13320:2009 standard, and the testing equipment can be a laser particle size analyzer (such as Malvern Master Size 3000).
[0143] When the volume distribution particle size Dv50 of the porous carbon skeleton meets the above range, the volume distribution particle size Dv50 of the silicon-carbon composite material is within an appropriate range, the structure of the silicon-carbon composite material is relatively stable, and the dynamic performance is relatively good, which is beneficial to improving the rate performance of the silicon-carbon composite material.
[0144] In some embodiments, the silicon-carbon composite material has a carbon layer on at least a portion of its surface.
[0145] In some embodiments, the carbon layer completely covers the outer surface of the porous carbon framework.
[0146] In some embodiments, the carbon layer covers a portion of the outer surface of the porous carbon skeleton.
[0147] The carbon layer coated on the outer surface of the porous carbon skeleton is beneficial to improving the conductivity of the silicon-carbon composite material and improving the rate performance of the material. At the same time, the carbon layer can also enhance the stability between the silicon-carbon composite material and the electrolyte and improve the cycle performance of the battery.
[0148] In some embodiments, the porous carbon framework includes one or more of graphite, soft carbon, and hard carbon.
[0149] In some embodiments, the porous carbon framework comprises hard carbon.
[0150] When the above material is prepared into a porous structure, it is beneficial for silicon particles to be arranged in the pores of the porous structure; and its structural stability is relatively high.
[0151] In some embodiments of the present application, a method for preparing a silicon-carbon composite material is provided, comprising the following steps:
[0152] Preparing a porous carbon skeleton containing a doping element, wherein the doping element satisfies: a lithium ion diffusion coefficient of the doping element at 25° C. is greater than a lithium ion diffusion coefficient of silicon at 25° C.;
[0153] Silicon-based materials are deposited between the pores of the porous carbon skeleton to obtain a silicon-carbon composite material.
[0154] On the one hand, the silicon-carbon composite material obtained by the above preparation method has a stable porous skeleton structure with strong supporting capacity, which is manifested as high stress capacity, and has excellent mechanical properties and conductivity; the pore structure in its porous carbon skeleton provides more space for setting silicon particles, which can be used for large-scale silicon storage; when the porous carbon skeleton is compounded with silicon particles, the silicon particles are not easy to agglomerate and can be evenly dispersed in the pores of the porous carbon skeleton; after the porous carbon skeleton is compounded with silicon particles, the conductivity of the silicon-carbon composite material can be improved, and the rate performance of the material can be improved. At the same time, the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and it can fully withstand the stress changes of silicon-based materials, ensure the structural stability of the silicon-carbon composite material, improve the cycle stability and lithium storage capacity of the silicon-carbon composite material, and extend the cycle life of the battery; on the other hand, doping the silicon-carbon composite material with an element whose lithium ion diffusion coefficient is greater than that of silicon element is beneficial to reducing the migration barrier and migration energy of lithium ions in the silicon-carbon composite material, greatly improving the lithium ion solid phase diffusion coefficient of the silicon-carbon composite material, improving the migration kinetics of lithium ions, and improving the battery rate performance.
[0155] In some embodiments, the preparation of the porous carbon framework includes solvent thermal reaction, activation pore formation and high temperature carbonization.
[0156] Solvothermal reaction: mixing a resin containing an unsaturated group and / or a sugar, a solvent, and an aqueous solution containing a doping element, and performing a solvothermal reaction to obtain a first product;
[0157] Activation pore creation: introducing water vapor into the first product to perform activation pore creation treatment to obtain the second product;
[0158] High-temperature carbonization: The second product is subjected to high-temperature carbonization treatment to obtain a porous carbon skeleton.
[0159] In the present application, the term "unsaturated group" refers to a group that can react with a hydroxyl group in a saccharide, including but not limited to an aldehyde group, a hydroxyl group, a carboxyl group or an acyl chloride group.
[0160] In the present application, the term "saccharide" refers to polyhydroxy (two or more) aldehyde or ketone compounds.
[0161] The above-mentioned method for preparing a porous carbon skeleton can obtain a porous carbon skeleton, which is beneficial for the subsequent deposition of silicon.
[0162] In some embodiments, the preparation of the porous carbon skeleton specifically includes solvent thermal reaction, activation pore formation and high temperature carbonization.
[0163] Solvothermal reaction: a resin containing an unsaturated group, a saccharide, a solvent, and an aqueous solution containing a doping element are mixed and subjected to a solvothermal reaction to obtain a first product;
[0164] Activation pore creation: introducing water vapor into the first product to perform activation pore creation treatment to obtain the second product;
[0165] High-temperature carbonization: The second product is subjected to high-temperature carbonization treatment to obtain a porous carbon skeleton.
[0166] In some embodiments, the resin containing unsaturated groups includes at least one of phenolic resin, furfural resin, and lignin-based activated carbon; and the sugar includes at least one of sucrose, glucose, and chitosan.
[0167] In this application, the term "phenolic resin" refers to a general term for a class of polymers prepared by the addition condensation reaction of phenolic compounds (such as phenol, cresol, xylenol, resorcinol, tert-butylphenol, bisphenol A, etc.) and aldehyde compounds (such as formaldehyde, acetaldehyde, paraformaldehyde, furfural, etc.) in the presence of alkaline or acidic catalysts.
[0168] In the present application, the term "furfural resin" refers to a furan resin polymer obtained by polycondensation or copolymerization using furfuryl alcohol or furfural as the main raw material.
[0169] In some embodiments, the resin containing unsaturated groups includes a phenolic resin, and the sugar includes sucrose. In some embodiments, the resin containing unsaturated groups includes a furfural resin, and the sugar includes sucrose. In some embodiments, the furfural resin containing unsaturated groups includes glucose. In some embodiments, the resin containing unsaturated groups includes a phenolic resin and a furfural resin, and the sugar includes glucose. In some embodiments, the resin containing unsaturated groups includes a phenolic resin, and the sugar includes sucrose and glucose.
[0170] In some embodiments, the phenolic resin includes at least one of a phenol-formaldehyde resin, a resorcinol-formaldehyde resin, and a hydroquinone-formaldehyde resin.
[0171] In some embodiments, the furfural resin comprises a phenol-furfural resin.
[0172] In some embodiments, the lignin-based activated carbon comprises alkali lignin activated carbon.
[0173] In some embodiments, the solvent comprises an alcohol and water, and the alcohol comprises at least one of ethanol, ethylene glycol, isopropanol, and n-butanol.
[0174] Alcohol and water serve as solvents for the resin containing unsaturated groups and sugars, respectively, promoting their dissolution in the solvent. At the same time, since alcohol and water are miscible, the dispersion between the resin containing unsaturated groups and sugars is improved, thereby improving the electrochemical properties of the final silicon-carbon composite material.
[0175] Resins and sugars, both of which have unsaturated groups, are used as raw materials. Through a solvent thermal reaction, they are fully cross-linked, and then subjected to high-temperature carbonization treatment to prepare hard carbon materials with spherical or quasi-spherical structures. Because the reactants dispersed in the solvent have high reactivity under the solvent thermal critical conditions, during the solvent thermal reaction, the long-chain structure of the resin containing unsaturated groups is rearranged, the hydroxyl groups in the sugar react with the unsaturated groups in the resin, and the product slowly crystallizes to obtain spherical or quasi-spherical particles with smooth surfaces. The resulting spherical or quasi-spherical porous carbon skeleton has the advantage of a shorter ion diffusion path and a larger interlayer spacing, which is conducive to the insertion / extraction and rapid migration of ions, and is conducive to the formation of a smooth void structure in the negative electrode film layer, thereby increasing the solid-phase diffusion rate and liquid-phase transmission performance of lithium ions, improving the fast charging capability of the battery, and improving the battery's rate performance.
[0176] In some embodiments, a resin containing an unsaturated group, a solvent, and an aqueous solution containing a doping element are mixed and subjected to a solvothermal reaction to obtain a first product, which is then carbonized to obtain a porous carbon skeleton.
[0177] In some embodiments, sugars, solvents, and an aqueous solution containing doping elements are mixed and subjected to a solvothermal reaction to obtain a first product, which is then carbonized to obtain a porous carbon skeleton.
[0178] By performing a solvothermal reaction on a single resin or sugar, a non-spherical or non-quasi-spherical porous carbon skeleton can be obtained. The preparation method is simple and is conducive to industrial promotion.
[0179] In some embodiments, the reaction temperature of the solvothermal reaction is 400°C-750°C.
[0180] In some embodiments, the reaction time of the solvothermal reaction is 4 h to 10 h.
[0181] In some embodiments, the reaction temperature of the solvothermal reaction can be selected as 400°C, 450°C, 500°C, 550°C, 600°C, 700°C, 750°C or a value in the range consisting of any two of the above points, and the reaction time can be selected as 4h, 5h, 6h, 7h, 8h, 9h, 10h or a value in the range consisting of any two of the above points.
[0182] By controlling the reaction temperature and reaction time in the solvent thermal reaction, the structural parameters of the porous carbon skeleton, such as the volume distribution particle size Dv50, specific surface area, pore size and pore volume, are within a suitable range, which is beneficial to the subsequent silicon deposition process. In addition, by controlling the reaction time and reaction temperature within a suitable range, the size of the grains formed by the doping elements can also be controlled within a suitable range, thereby improving the rate performance and cycle performance of the material.
[0183] In some embodiments, the mass ratio of the resin containing unsaturated groups to the saccharide is (2:8)-(9:1), and can be optionally (4:6)-(6:4).
[0184] In some embodiments, the mass ratio of the resin containing unsaturated groups to the saccharide can be 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1 or a value in the range consisting of any two of the above points.
[0185] In some embodiments, the mass ratio of the resin containing unsaturated groups to the saccharide is (4:6)-(6:4). In some embodiments, the mass ratio of the resin containing unsaturated groups to the saccharide is 4:6, 5:5, 6:4, or a value within a range consisting of any two of the above values.
[0186] The molar ratio of the resin containing unsaturated groups to the saccharide is controlled within a suitable range so that the porous carbon skeleton has a suitable specific surface area, pore size, pore volume and particle size, which is beneficial to the subsequent deposition of silicon or element doping process.
[0187] In some embodiments, the treatment temperature for activation pore formation is 400°C-500°C.
[0188] In some embodiments, the activation pore-forming treatment time is 4 h to 8 h.
[0189] In some embodiments, the flow rate of water vapor is 0.5 g / min to 1 g / min.
[0190] By controlling the activation hollowing treatment temperature, treatment time, and water vapor flow rate within appropriate ranges, the pore size and pore volume in the porous carbon skeleton can be within appropriate ranges, thereby obtaining a porous carbon skeleton with excellent structural properties.
[0191] In some embodiments, the carbonization treatment time is 400° C.-700° C., and the carbonization treatment temperature is 4 h-12 h.
[0192] In some embodiments, vapor phase silicon deposition specifically includes:
[0193] In a nitrogen or argon atmosphere, silicon-containing gas is used as a silicon source to perform vapor deposition on the porous carbon skeleton.
[0194] In some embodiments, silicon deposition specifically includes:
[0195] In a nitrogen or argon atmosphere, silicon-containing gas is used as a silicon source, and vapor containing a doping element is used as a doping element source to perform vapor deposition on a porous carbon skeleton.
[0196] In some embodiments, the silicon-containing gas includes one or more of monosilane, trisilane, dichlorosilane, trichlorosilane, and tetrachlorosilane.
[0197] In some embodiments, the flow rate of the silicon-containing gas is 0.5-30 L / min.
[0198] In some embodiments, the flow rate of nitrogen or argon is 0.5-30 L / min.
[0199] In some embodiments, the deposition temperature of the vapor deposited silicon is 500°C to 900°C.
[0200] In some embodiments, the deposition time of vapor deposited silicon is 6-24 hours.
[0201] Silicon deposition is carried out under appropriate reaction conditions so that silicon is evenly dispersed in the pores of the porous carbon skeleton, thereby improving the structural properties of the silicon-carbon composite material and the rate performance of the material.
[0202] In some embodiments, the preparation method further comprises preparing a carbon layer,
[0203] Preparation of carbon layer: performing carbon coating treatment on the surface of silicon-carbon composite material.
[0204] In some embodiments, the carbon coating process includes any one of chemical vapor deposition carbon coating, pyrolysis carbon coating, hydrothermal carbon coating, and polyelectrolyte modification carbon coating.
[0205] The carbon layer covering the surface of the silicon-carbon composite material is beneficial to improving the conductivity of the silicon-carbon composite material and improving the rate performance of the material. At the same time, the carbon layer can also enhance the stability between the silicon-carbon composite material and the electrolyte and improve the cycle performance of the battery.
[0206] In one embodiment of the present application, a secondary battery is provided.
[0207] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0208] [Positive electrode]
[0209] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0210] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0211] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0212] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0213] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0214] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0215] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0216] [Negative electrode]
[0217] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. The negative electrode film layer includes a negative electrode active material. The negative electrode active material includes a silicon-carbon composite material in some embodiments.
[0218] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0219] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0220] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0221] In some embodiments, the mass content of the silicon-carbon composite material is greater than or equal to 20%, based on the total mass of the negative electrode active material.
[0222] In some embodiments, based on the total mass of the negative electrode active material, the mass content of the silicon-carbon composite material can be selected as any one of greater than or equal to 20%, greater than or equal to 25%, greater than or equal to 30%, greater than or equal to 35%, greater than or equal to 40%, greater than or equal to 45%, greater than or equal to 50%, greater than or equal to 55%, greater than or equal to 60%, greater than or equal to 65%, greater than or equal to 70%, greater than or equal to 75%, greater than or equal to 80%, greater than or equal to 85%, greater than or equal to 90%, and greater than or equal to 95%.
[0223] The silicon-carbon composite material is controlled within a suitable range so that its battery has excellent energy density and cycle performance.
[0224] In some embodiments, the mass content of the silicon-carbon composite material is 25%-90%, based on the total mass of the negative electrode active material.
[0225] In some embodiments, based on the total mass of the negative electrode active material, the mass content of the silicon-carbon composite material can be selected as 25%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or a value in the range consisting of any two of the above points.
[0226] By controlling the silicon-carbon composite material within an appropriate range, the energy density and cycle life of the battery can be taken into account, and the electrochemical performance of the battery can be comprehensively improved.
[0227] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0228] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0229] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0230] In some embodiments, the compacted density of the negative electrode sheet is 1.2 g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3, 1.5g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 Or a value within the range formed by any two of the above points.
[0231] By controlling the compaction density of the negative electrode sheet within a suitable range, the battery has excellent energy density.
[0232] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0233] [Electrolytes]
[0234] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0235] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.
[0236] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0237] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0238] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0239] [Isolation film]
[0240] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0241] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0242] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0243] In some embodiments, a secondary battery includes a positive electrode sheet, an electrolyte, a separator, and a negative electrode sheet in some embodiments.
[0244] In some embodiments, the secondary battery comprises a lithium-ion battery.
[0245] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0246] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0247] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 5 with a square structure as an example.
[0248] In some embodiments, the energy density of the secondary battery is 400-550 Wh / kg.
[0249] In some embodiments, referring to Figure 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0250] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0251] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0252] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0253] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0254] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0255] In addition, the present application also provides an electric device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0256] As the electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0257] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0258] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0259] Example
[0260] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0261] The lithium ion diffusion coefficient data of the simple substance of each doping element and the simple substance of silicon used in the following examples are as follows:
[0262] The lithium ion diffusion coefficient of Sn element at 25℃ is 1×10 -13 cm 2 / S;
[0263] The lithium ion diffusion coefficient of Ge element at 25℃ is 5×10 -14 cm 2 / S;
[0264] The lithium ion diffusion coefficient of Sb element at 25℃ is 7×10 -14 cm 2 / S;
[0265] The lithium ion diffusion coefficient of Bi element at 25℃ is 4×10 -13 cm 2 / S;
[0266] The lithium ion diffusion coefficient of Sr element at 25℃ is 6×10 -13 cm 2 / S;
[0267] The lithium ion diffusion coefficient of element B at 25°C is 10 -16 cm 2 / S;
[0268] The lithium ion diffusion coefficient of silicon at 25°C is 2×10 -15 cm 2 / S.
[0269] 1. Preparation method
[0270] Example 1
[0271] (1) Preparation of positive electrode sheet
[0272] The positive electrode active material LiNi0.95 Co 0.04 Mn 0.01 O2 (NCM), conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are added with N-methylpyrrolidone in a mass ratio of 97%:1%:2% and mixed evenly to obtain a positive electrode slurry; then it is coated on the positive electrode collector, dried, cold pressed, and cut to obtain a positive electrode sheet.
[0273] (2) Preparation of negative electrode sheet
[0274] 1) Preparation of silicon-carbon composite materials
[0275] 500g of phenolic resin was evenly dispersed in 2000ml of ethanol, and 500g of sucrose was dissolved in water and stirred to obtain a mixed solution. 30g of tin sulfate was dissolved in 100g of water to obtain an aqueous solution, which was added to the mixed solution and stirred for 30 minutes. The mixed solution was placed in a reactor and reacted at 600°C for 8 hours to obtain a powder. Water vapor was then introduced at 450°C for 6 hours to activate pore formation, with the water vapor flow rate of 1g / min. The treated product was placed in a muffle furnace under nitrogen protection and carbonized at 1200°C for 4 hours to obtain a spherical or quasi-spherical porous carbon framework.
[0276] A silicon-carbon composite material was obtained by vapor deposition in a tube furnace using monosilane as a silicon source and nitrogen as a protective gas. The flow rate of monosilane was 0.06 L / min, the flow rate of the protective gas was 4 L / min, the temperature of the vapor deposition was 450°C, and the deposition time was 6 hours.
[0277] Using methane as the carbon source and nitrogen as the protective gas, vapor deposition of the carbon source was carried out in a tubular furnace, wherein the flow rate of methane was 6 L / min, the flow rate of the protective gas was 15 L / min, the vapor deposition temperature was 900°C, the time was 6 h, and the gas source was turned off to cool down to obtain a silicon-carbon composite material.
[0278] 2) Preparation of negative electrode sheet
[0279] Graphite and the silicon-carbon composite material prepared in step 1) are mixed in a mass ratio of 3:7 to obtain a negative electrode active material, wherein the mass fraction of the silicon-carbon composite material is 70% based on the total mass of the negative electrode active material.
[0280] The mixed negative electrode active material, conductive agent carbon black, carbon nanotubes (CNT), binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are added to deionized water in a weight ratio of 94.5%:1%:0.375%:2.8%:1.325% and mixed evenly to obtain a negative electrode slurry; the slurry is coated on the negative electrode current collector, and the negative electrode sheets are obtained after drying, cold pressing, and slitting.
[0281] (3) Isolation film
[0282] Polypropylene film is used as the isolation film.
[0283] (4) Preparation of electrolyte
[0284] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, and fluoroethylene carbonate (FEC) were mixed in a volume ratio of 1:1:1:1, and LiPF6 was added and dissolved in the organic solvent and stirred evenly to make the concentration of the electrolyte 1 mol / L to obtain the electrolyte of Example 1.
[0285] (5) Preparation of batteries
[0286] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a battery cell, the battery cell is welded with the electrode ears, and the battery cell is placed in an aluminum shell, and then the electrolyte is injected and sealed. After standing, cold pressing, formation, shaping, capacity testing and other processes, a lithium-ion secondary battery is obtained.
[0287] Example 2-3
[0288] The preparation parameters in Example 2-3 are basically the same as those in Example 1, but the preparation parameters of the silicon-carbon composite material are adjusted. The specific parameters are shown in Table 1.
[0289] Examples 4-7
[0290] The preparation parameters in Examples 4-7 are basically the same as those in Example 1, except that the preparation parameters of the silicon-carbon composite material are adjusted, and the tin sulfate in Example 1 is replaced with germanium sulfate, antimony sulfate, bismuth sulfate, or tin sulfate + antimony sulfate.
[0291] Examples 8-13
[0292] The preparation parameters in Examples 8-13 are basically the same as those in Example 1, except that the preparation parameters of the silicon-carbon composite material are adjusted, and the mass of tin sulfate in Examples 10 and 12 is adjusted to 10 g and 70 g, respectively. The carbon source in Example 13 is sucrose, and the prepared porous carbon skeleton has a non-spherical or non-spherical structure, as follows:
[0293] 1) Preparation of silicon-carbon composite materials
[0294] 500 g of sucrose was dissolved in water and stirred evenly to obtain a mixed solution, 30 g of tin sulfate was dissolved in 100 g of water to obtain an aqueous solution, the aqueous solution was added to the mixed solution and stirred for 30 minutes, the mixed solution was placed in a reactor and reacted at 600°C for 8 hours to obtain a powder, and then water vapor was introduced at 450°C for 6 hours for activation and pore formation treatment, wherein the water vapor flow rate was 1 g / min, and the treated product was placed in a muffle furnace under nitrogen protection and carbonized at a temperature of 1200°C for 4 hours to obtain a non-spherical or non-spherical porous carbon skeleton.
[0295] A silicon-carbon composite material was obtained by vapor deposition in a tube furnace using monosilane as a silicon source and nitrogen as a protective gas. The flow rate of monosilane was 0.06 L / min, the flow rate of the protective gas was 4 L / min, the temperature of the vapor deposition was 450°C, and the deposition time was 6 hours.
[0296] Using methane as the carbon source and nitrogen as the protective gas, vapor deposition of the carbon source was carried out in a tubular furnace, wherein the flow rate of methane was 6 L / min, the flow rate of the protective gas was 15 L / min, the vapor deposition temperature was 900°C, the time was 6 h, and the gas source was turned off to cool down to obtain a silicon-carbon composite material.
[0297] Comparative Example 1-2
[0298] The preparation parameters in Comparative Example 1-2 are basically the same as those in Example 1, but the preparation parameters of the silicon-carbon composite material are adjusted. The specific parameters are shown in Table 1. The specific preparation method is as follows:
[0299] Comparative Example 1: The difference from Example 1 is that tin sulfate is replaced by boric acid.
[0300] Comparative Example 2: The difference from Example 1 is that tin sulfate is not added.
[0301] 2. Performance Testing
[0302] 1. Lithium ion diffusion coefficient of each element
[0303] (1) Preparation of button cell: Mix the single material formed by each doping element or silicon element, binder, and conductive agent in a ratio of 8:1:1 and add them to deionized water, mix and stir evenly to obtain negative electrode slurry; apply the negative electrode slurry on one surface of the negative electrode current collector copper foil, dry, cold press, and cut to obtain negative electrode sheets, and use a punching die to obtain a certain area (this application uses 153.86mm 2) negative electrode disc. A metallic lithium sheet was used as the counter electrode, a PP film was used as the separator, and the electrolyte formulation was: ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, and FEC were mixed in a volume ratio of 1:1:1:1 to form a solvent. LiPF6 was dissolved in the solvent as the lithium salt to prepare a solution with a concentration of 1 mol / L. The cells were assembled into CR2032 button cells in an argon-protected glove box.
[0304] (2) The lithium ion diffusion coefficient of the single-substance material formed by each doping element or silicon element is calculated according to the following formula: D Li =1 / (1000×S×Z iq ),
[0305] Where: D Li is the lithium ion diffusion coefficient; S is the area of the small disc in the button battery prepared above; Z iq is the specific capacity of each elemental material;
[0306] Among them, Z iq The following test steps can be used: at 25 ° C, use a 0.1C current to charge the button battery prepared above at a constant current until the battery voltage is less than 0.05V, and then let it stand for 120 minutes; then use a 0.1C current to discharge the button battery prepared above at a constant current until the battery voltage is greater than 1.5V, and measure the specific capacity of the button battery at this time and record it as Z iq .
[0307] 2. Test of grain size formed by doping elements in silicon-carbon composite materials
[0308] The grain size of the carbon-silicon composite material formed by the doping elements was measured using an X-ray powder diffractometer (XRD). The X'pertPROo from the United States was used to measure the grain size. The detailed test process for the grain size is as follows:
[0309] a. Measurement of the measured width Bm of the silicon-carbon composite material sample. Set the instrument scanning rate to 2 degrees / minute, obtain the XRD spectrum of the sample to be tested, and use JADE software to subtract the CuKa2 background to obtain the Bm of each diffraction peak;
[0310] b. Instrument width Bs measurement. Use the same material and grain size as the silicon-carbon composite material sample. The XRD pattern of the standard sample was measured under the same experimental conditions as the silicon-carbon composite material sample, and Bs was obtained from the pattern;
[0311] c. Calculation of half-height width B. B = Bm - Bs; (Note: If the unit of B is calculated as angle, it needs to be converted into radians)
[0312] d. Calculation of grain size: Use the Scherrer formula D = Kλ / Bcosθ, where K is 0.89, θ is the diffraction angle, λ = 0.154056nm, and substitute B to obtain the grain thickness in the normal direction of the crystal plane represented by a single diffraction peak. Take multiple diffraction peaks and calculate the average value to obtain the grain size.
[0313] 3. Mass content of doping elements, silicon-based materials, and porous carbon skeletons
[0314] The measurement is carried out with reference to the EPA 6010D-2014 standard; specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used. The sample to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then restored to the ground state from the excited state. In the above process, energy is released and recorded as different characteristic spectral lines, which are used for quantitative analysis of doping elements, silicon-based materials and porous carbon skeletons.
[0315] 4. Battery 40% SOC discharge time
[0316] The battery cell was discharged at a constant current of 0.33C to 2.8V and allowed to stand for 30 minutes; charged at a constant current of 0.33C to 4.25V and then at a constant voltage of 0.05C until the voltage stabilized and allowed to stand for 30 minutes; discharged at a constant current of 0.33C to 2.8V, at which time the initial capacity C0 was read and allowed to stand for 30 minutes; charged at a constant current of 0.33C to 4.25V and then at a constant voltage of 0.05C until the voltage stabilized and allowed to stand for 30 minutes; discharged at a constant current of 0.33C to 0.4C0Ah (40%) SOC and allowed to stand for 60 minutes; discharged at a constant current of 4.5C to 2.8V and recorded the discharge time.
[0317] 5. Battery fast charging time
[0318] At 25°C, the batteries of each embodiment and comparative example were charged and discharged for the first time at a current of 1C (i.e., the current value at which the rated capacity is completely discharged within 1 hour). Specifically, the battery was charged at a constant current rate of 1C to a voltage of 4.3V, then charged at a constant voltage to a current of ≤0.05C, allowed to stand for 5 minutes, and then discharged at a constant current rate of 0.33C to a voltage of 2.8V. The actual capacity was recorded as C0.
[0319] Then the battery is charged with constant current at 2.0C0, 2.5C0, 3.0C0, 3.5C0, 4.0C0, 4.5C0, 5.0C0, 5.5C0 in sequence to the full battery charge cut-off voltage of 4.3V or the negative electrode cut-off potential of 0V (whichever is reached first). After each charging is completed, it is necessary to discharge it with 1C0 to the full battery discharge cut-off voltage of 2.8V. The negative electrode potential corresponding to charging to 10%, 20%, 30%, ..., 80% SOC (State of Charge) at different charge rates is recorded, and the charge rate-negative electrode potential curve under different SOC states is drawn. After linear fitting, the charge rate corresponding to the negative electrode potential of 0V under different SOC states is obtained. The charge rate is the charging window under the SOC state, which is recorded as C 20% SOC, C 30% SOC, C 40% SOC, C 50% SOC, C 60% SOC, C 70% SOC, C 80% SOC, according to the formula (60 / C 20% SOC+60 / C 30% SOC+60 / C 40% SOC+60 / C 50% SOC+60 / C 60% SOC+60 / C 70% SOC+60 / C 80% The charging time T for charging the battery from 10% SOC to 80% SOC is calculated by multiplying the SOC by 10% to get the charging time (in minutes). The shorter the charging time, the better the fast charging performance of the battery.
[0320] 6. Battery 25℃ cycle performance test
[0321] The secondary batteries prepared in each example and comparative example were charged at a constant current rate of 0.5C to a charge cutoff voltage of 4.25V, then charged at a constant voltage rate to a current of ≤0.05C, allowed to rest for 5 minutes, and then discharged at a constant current rate of 0.33C to a discharge cutoff voltage of 2V, allowed to rest for 5 minutes. This constituted one charge-discharge cycle. The batteries were subjected to cyclic charge-discharge testing using this method until the battery capacity decayed to 80%. The number of cycles at this point is the battery's cycle life at 25°C.
[0322] 3. Analysis of test results of various embodiments and comparative examples
[0323] Batteries of various embodiments and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1, 2, and 3 below.
[0324] Table 1
[0325] Table 2
[0326] Table 3
[0327] According to the above results, the silicon-carbon composite materials in Examples 1-13 all include a porous carbon skeleton; a silicon-based material, at least part of which is arranged in the pores of the porous carbon skeleton; and the porous carbon skeleton includes at least one of the doping elements Sn, Ge, Sb, and Bi, and the lithium ion diffusion coefficient of the single substance of Sn, Ge, Sb or Bi at 25°C is greater than the lithium ion diffusion coefficient of the single substance of silicon at 25°C.
[0328] From the comparison of Examples 1-13 and Comparative Examples 1-2, it can be seen that the silicon-carbon composite material of the present application is beneficial to reducing the fast charging time of the battery, extending the discharge time of the battery, improving the rate performance of the battery, increasing the number of cycles of the battery, and extending the cycle life of the battery.
[0329] From the comparison of Examples 1, 4-7 and Comparative Examples 1-2, it can be seen that the doping elements include one or two of Sn, Ge, Sb, and Bi, which are beneficial to increasing the number of battery cycles and 40% SOC discharge time, reducing the fast charging time of the battery, and improving the battery's cycle performance and rate performance.
[0330] From the comparison of Examples 8-9 and 11 with Example 1, it can be seen that controlling the grain size to be less than or equal to 10 nm is beneficial to increasing the number of battery cycles and the 40% SOC discharge time, reducing the fast charge time of the battery, and improving the battery's rate performance and cycle performance. From the comparison of Examples 8 and 11 with Examples 1 and 9, it can be seen that further controlling the grain size to 3 nm to 7 nm is beneficial to further increasing the number of battery cycles and the 40% SOC discharge time, reducing the fast charge time of the battery, and further improving the battery's rate performance and cycle performance.
[0331] As can be seen from Examples 10-12, based on the total mass of the silicon-carbon composite material, the mass fraction of the doping element is controlled to be less than or equal to 7%, so that the battery has a shorter fast charge time, a longer discharge time and a larger number of cycles, so that the battery has excellent rate performance and cycle performance. As can be seen from the comparison of Examples 10-11 with Example 12, controlling the mass fraction of the doping element to 1%-3% is conducive to further improving the number of battery cycles and 40% SOC discharge time, reducing the fast charge time of the battery, and further improving the rate performance and cycle performance of the battery.
[0332] From the comparison between Examples 1-3 and Example 13, it can be seen that the porous carbon skeleton is spherical or quasi-spherical, which is beneficial to further improve the 40% SOC discharge time and reduce the fast charging time of the battery, improve the battery's rate performance, and extend the battery's cycle life.
[0333] From the comparison between Example 1-2 and Example 3, it can be seen that controlling the volume distribution particle size Dv50 of the silicon-carbon composite material to be less than or equal to 5μm is beneficial to further improve the 40% SOC discharge time and reduce the fast charging time of the battery, improve the battery's rate performance, improve the battery's cycle life, and improve the battery's cycle performance. From the comparison between Example 1 and Examples 2-3, it can be seen that controlling the volume distribution particle size Dv50 of the silicon-carbon composite material to be 1μm-3μm is beneficial to further improve the 40% SOC discharge time and reduce the battery's fast charging time, improve the battery's rate performance, and improve the battery's dynamic performance.
[0334] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A silicon-carbon composite material, comprising: Porous carbon framework; A silicon-based material, at least part of which is disposed in the pores of the porous carbon skeleton; as well as A doping element, at least part of which is distributed in the porous carbon skeleton; The doping element satisfies that: the lithium ion diffusion coefficient of the doping element alone at 25° C. is greater than the lithium ion diffusion coefficient of silicon alone at 25° C.
2. The silicon-carbon composite material according to claim 1, characterized in that: The lithium ion diffusion coefficient of the doping element at 25°C is greater than 10 - 14 cm 2 / S, can be greater than 10 -14 cm 2 / S and less than or equal to 10 -13 cm 2 / S; and / or, The lithium ion diffusion coefficient of the silicon element at 25°C is less than 10 -14 cm 2 / S, can be greater than 10 -15 cm 2 / S and less than 10 -14 cm 2 / S.
3. The silicon-carbon composite material according to claim 1 or 2, characterized in that: The doping element includes at least one of Sn, Ge, Sb, Bi, and Sr.
4. The silicon-carbon composite material according to any one of claims 1 to 3, characterized in that: At least part of the doping elements forms grains in the silicon-carbon composite material; Optionally, the size of the grains is less than or equal to 10 nm, and more optionally 3 nm-7 nm.
5. The silicon-carbon composite material according to any one of claims 1 to 4, characterized in that: Based on the total mass of the silicon-carbon composite material, the mass fraction of the doping element is less than or equal to 7%, and can be optionally 1%-3%.
6. The silicon-carbon composite material according to any one of claims 1 to 5, characterized in that: The porous carbon skeleton is spherical or quasi-spherical.
7. The silicon-carbon composite material according to any one of claims 1 to 6, characterized in that: Based on the total mass of the silicon-carbon composite material, the mass fraction of the silicon-based material is greater than or equal to 30%, and can be optionally 35%-50%; and / or, Based on the total mass of the silicon-carbon composite material, the mass fraction of the porous carbon skeleton is greater than or equal to 30%, and can be optionally 40%-60%.
8. The silicon-carbon composite material according to any one of claims 1 to 7, characterized in that: The volume distribution particle size Dv50 of the silicon-carbon composite material is less than or equal to 5 μm, and can be selected to be 1 μm-3 μm.
9. The silicon-carbon composite material according to any one of claims 1 to 8, characterized in that: The silicon-carbon composite material satisfies at least one of the following (1)-(4): (1) The specific surface area of the porous carbon skeleton is 1000 m 2 / g-2500m 2 / g; (2) The pore size of the porous carbon skeleton is 0.5 nm-100 nm; (3) The pore volume of the porous carbon skeleton is 0.5 cm 3 / g-8.5cm 3 / g; (4) The volume distribution particle size Dv50 of the porous carbon skeleton is 0.3 μm-5 μm.
10. The silicon-carbon composite material according to any one of claims 1 to 9, characterized in that: The silicon-carbon composite material has a carbon layer on at least a portion of its surface.
11. A method for preparing a silicon-carbon composite material, characterized in that: The steps include: Preparing a porous carbon skeleton containing a doping element, wherein the doping element satisfies: a lithium ion diffusion coefficient of a single substance of the doping element at 25° C. is greater than a lithium ion diffusion coefficient of a single substance of silicon at 25° C.; The silicon-carbon composite material is obtained by depositing a silicon-based material in the pores of the porous carbon skeleton.
12. The preparation method according to claim 11, characterized in that: The preparation of the porous carbon skeleton includes solvent thermal reaction, activation pore formation and high temperature carbonization; Solvothermal reaction: mixing a resin containing an unsaturated group and / or a sugar, a solvent, and an aqueous solution containing a doping element, and performing a solvent thermal reaction to obtain a first product; Activation pore formation: introducing water vapor into the first product to perform activation pore formation treatment to obtain a second product; High temperature carbonization: The second product is subjected to high temperature carbonization treatment to obtain a porous carbon skeleton.
13. The preparation method according to claim 12, characterized in that: The reaction temperature of the solvent thermal reaction is 400° C.-750° C.; and / or the reaction time of the solvent thermal reaction is 4 h-10 h.
14. The preparation method according to claim 12 or 13, characterized in that: The mass ratio of the resin containing unsaturated groups to the sugar is (2:8)-(9:1), and can be optionally (4:6)-(6:4).
15. The preparation method according to any one of claims 12 to 14, characterized in that: The resin containing unsaturated groups includes at least one of phenolic resin, furfural resin, and lignin-based activated carbon; and / or the sugar includes at least one of sucrose, glucose, and chitosan.
16. The preparation method according to any one of claims 12 to 15, characterized in that: The activation pore-forming treatment temperature is 400° C.-500° C.; and / or, The activation pore-forming treatment time is 4h-8h; and / or, The flow rate of the water vapor is 0.5 g / min-1 g / min.
17. The preparation method according to any one of claims 11 to 16, characterized in that: The deposition temperature of the vapor deposited silicon is 500° C.-900° C.; and / or, the deposition time of the vapor deposited silicon is 6 h-24 h.
18. The preparation method according to any one of claims 11 to 17, characterized in that: The preparation method further comprises preparing a carbon layer: performing a carbon coating treatment on the surface of the silicon-carbon composite material.
19. A secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer arranged on the surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon composite material as described in any one of claims 1 to 10 or a silicon-carbon composite material prepared by the preparation method as described in any one of claims 11 to 18.
20. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 19.